Cryptosexuality and the genetic diversity paradox in coffee rust, Hemileia vastatrix. - Carlos Roberto Carvalho (Public Library of Science (PLoS), 2011)
Background Despite the fact that coffee rust was first investigated scientifically more than a century ago, and that the disease is one of the major constraints to coffee production--constantly changing the socio-economic and historical landscape of the crop--critical aspects of the life cycle of the pathogen, Hemileia vastatrix, remain unclear. The asexual urediniospores are regarded as the only functional propagule: theoretically, making H. vastatrix a clonal species. However, the well-documented emergence of new rust pathotypes and the breakdown in genetic resistance of coffee cultivars, present a paradox. Methods and results Here, using computer-assisted DNA image cytometry, following a modified nuclear stoichiometric staining technique with Feulgen, we show that meiosis occurs within the urediniospores. Stages of spore development were categorised based on morphology, from the spore-mother cell through to the germinating spore, and the relative nuclear DNA content was quantified statistically at each stage. Conclusions Hidden sexual reproduction disguised within the asexual spore (cryptosexuality) could explain why new physiological races have arisen so often and so quickly in Hemileia vastatrix. This could have considerable implications for coffee breeding strategies and may be a common event in rust fungi, especially in related genera occupying the same basal phylogenetic lineages.